Pseudomembranous collagenous colitis: an unusual cause of chronic diarrhoea. (13th February 2014) - Khan-Kheil, Ayisha Mehtab; Disney, Benjamin; Ruban, Ernie; Wood, Gordon
Abstract : An 81-year-old woman presented with a history of severe chronic diarrhoea resulting in an admission with syncope and electrolyte abnormalities. Imaging studies of the bowel were normal. However, biopsies taken during colonoscopy enabled a diagnosis to be made and effective treatment to be initiated. This case report details the presentation, diagnosis and management of a rare injury pattern affecting the bowel: pseudomembranous collagenous colitis.